Women’s thalassemia status and embryo carrier status do not affect pregnancy outcomes after euploid transfers - Fan, Li; Li, Zhetao; Li, Wugao; Wei, Liuyan; Tang, Ni; Nong, Liuying; Li, Jingjing; Huang, Wenjie (Frontiers in Endocrinology, 2025)
BackgroundWhile preimplantation genetic testing for monogenic disorders (PGT-M) is widely applied to prevent transmission of severe thalassemia, limited evidence exists regarding the impact of thalassemia carrier status or embryo genotype on pregnancy outcomes in patients undergoing preimplantation genetic testing for aneuploidy (PGT-A).MethodsThis retrospective cohort study included 981 women who underwent their first autologous IVF cycle with single euploid embryo transfer at a tertiary reproductive center between January 2016 and December 2023. Among them, 512 were classified as having thalassemia (including heterozygous carriers and non–transfusion-dependent cases), and 460 were non-thalassemia controls. All participants underwent PGT-A, with a subset also receiving concurrent PGT-M. Clinical outcomes—including clinical pregnancy, live birth, and miscarriage rates—were compared between groups using Poisson regression models, adjusting for age, BMI, and endometrial thickness. Additional subgroup analyses stratified patients by age (<35 vs. ≥35 years) and embryo genotype (thalassemia carrier vs. non-carrier).ResultsThalassemia patients were significantly younger and had lower BMI and thicker endometrium compared to non-thalassemia patients. However, no statistically significant differences were found in clinical pregnancy (67.8% vs. 63.0%, aRR = 1.05, 95% CI: 0.94–1.16), live birth (61.9% vs. 53.3%, aRR = 1.08, 95% CI: 0.96–1.23), or miscarriage rates (5.9% vs. 9.8%, aRR = 0.82, 95% CI: 0.49–1.40) between the groups after adjustment. Furthermore, within the broadly defined thalassemia group, no significant differences were observed between embryos with and without pathogenic thalassemia variants. Interaction analyses showed no synergistic effects between thalassemia status and clinical variables.ConclusionThalassemia status and embryo genotype do not appear to adversely affect pregnancy outcomes following euploid embryo transfer. These findings support the transfer of heterozygous carrier embryos and suggest that individualized reproductive counseling and embryo selection strategies can be safely applied in couples at genetic risk of thalassemia undergoing IVF with PGT.